До історії вивчення навершь скіфського часу - Фрунт, О.С. (Археологія і давня історія України, 2021)
Представлено історіографічний огляд вивчення металевих навершь VII—IV ст. до н. е. як однієї з найбільш своєрідних категорій, пов’язаних з племенами Східної та Центральної Європи скіфського часу. Виділяються основні періоди дослідження: перший (1850—1940-ві рр.), другий (1950—1980-ті рр.) і третій (з 1990-х рр. до сьогодення). Metal pole-tops of the 7th—4th centuries BC is one of the most wander materials associated with the tribes of the Eastern and Central Europe of the Scythian Age. However, opinions on their function are diverse. Now the pole-tops have a rather general name reflecting the purpose of these objects only approximately. Nevertheless, the study of these artifacts allow us to distinguish three periods: the first (1850—1940s), the second (1950—1980s) and the third (from the 1990s to the present). The first period (1950—1980s) begins with the excavations by I. E. Zabelin of steppe aristocratic barrows. In such barrows as Krasnokutsky, Slonovskaya Bliznitsa, Chertomlyk, a lot of Scythian pole-tops have been discovered. Thanks to localization of the finds in the burials I. E. Zabelin was able to suggest the function of these objects. He believed that the pole-tops could be the decoration of carts, nomadic tents on a chariot. The period is associated with the works of A. S. Lappo- Danilevsky, E. Minns, I. I. Tolstoy and N. P. Kondakov, J. Hampel, P. Reinicke, L. Marton et al. The result was summed up in the research of M. I. Rostovtsev. He supports the idea of a funerary vehicle and connects the origin of the finds with Hittite and Assyrian art, Transcaucasian tombs. In the second period (1950—1980s) there is a noticeable intensity of research on Scythian pole-tops, systematization of artifacts and the use of new approaches to the study. The typology proposed at this time is still used in research now. Almost all finds known at the end of the 70s were systematized in the paper by E. V. Perevodchikova. Different approaches were used in order to interpret the meaning of the pole-tops: as a part of the drawbar of a chariot (V. V. Shleev), shamanic musical instruments (K. Bakai), as the embodiment of the idea of a world tree which marks the ritual space (E. V. Perevodchikova, D. S. Raevsky). V. A. Ilyinskaya considered these artifacts to be multifunctional. The study of the chemical composition of the metal by T. B. Bartseva is important, since it demonstrates the existence of several production centers and sheds light on the origin of the finds. In the third period (from the 1990s to the present) the issue of the functional purpose and origin of the Scythian pole-tops was clarified. The scholars consider them the indicators, marking the arrival of Scythians in North Caucasus and North Pontic region (V. I. Klochko, V. Yu. Murzin, A. Yu. Alekseev, S. A. Skory, D. S. Grechko). T. V. Ryabkova connects the origin of the spherical pole-tops with the eastern territories considering these finds to be purely nomadic. N. L. Chlenova, M. M. Pogrebova, M. Castelluccia, R. Dan lead the line of origin of Scythian pole-tops from the rattles of Iran and Transcaucasia. The study of the technology of making bronze finds and their designs shows that they were cast on a lost wax model or in bivalve molds. In the interpretation of the function of Scythian pole-tops in the period of the 1990s—2010s the researchers depending on the context of discovery correlate these objects from burials with carts (Yu. V. Boltryk) or wooden poles that limited the ritual space for sacrifices (A. R. Kantorovich, V. R. Erlikh). H. Parzinger and S. Hasanov associate their use with shamanism. Thus, the history of the study of Scythian pole-tops made it possible to highlight topical issues. These are the origin and function, improvement of typology using new methods, clarification of chronology, correlation of the distribution of finds with key events in history in Eastern and Central Europe during the Scythian Age.